Digital twin : a dynamic system and computing perspective - Ganguli, Ranjan; Adhikari, Sondipon; Chakraborty, Souvik; Ganguli, Mrittika (Boca Raton : CRC Press, 2023)
The digital twin of a physical system is an adaptive computer analog which exists in the cloud and adapts to changes in the physical system dynamically. This book introduces the computing, mathematical, and engineering background to understand and develop the concept of the digital twin. It provides background in modeling/simulation, computing technology, sensor/actuators, and so forth, needed to develop the next generation of digital twins. Concepts on cloud computing, big data, IoT, wireless communications, high-performance computing, and blockchain are also discussed. Features: Provides background material needed to understand digital twin technology Presents computational facet of digital twin Includes physics-based and surrogate model representations Addresses the problem of uncertainty in measurements and modeling Discusses practical case studies of implementation of digital twins, addressing additive manufacturing, server farms, predictive maintenance, and smart cities This book is aimed at graduate students and researchers in Electrical, Mechanical, Computer, and Production Engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Digital twins (Computer simulation); Cooperating objects (Computer systems); COMPUTERS / Networking / General; MATHEMATICS / General; TECHNOLOGY / Electricity